Efecto de la mortalidad por homicidio con respecto a la mortalidad general - Marie Gisele Coutin; Pardo Torres Myriam Patricia; Núñez Gómez Nicolás Arturo (Universidad Nacional de Colombia, 2002)
This text is an analysis of the effect of mortality in Colombia due to violence compared to other types of death from 1973 to 1996. This study uses different statistic measures such as data, rates per thousand inhabitants/ year, residual and structural rate, and proportional mortality to achieve the analysis. The results allow to conclude that mortality due to violence does not allow to express achievements in the area of health, in social progress and contributions o public health for those years. Se presenta un análisis del efecto de la mortalidad por homicidio en Colombia sobre la mortalidad general en los años 1973 a 1996. Para lograr este objetivo se utilizan los datos, tasas por mil habitantes/año, razón, tipificación directa, razón residual/estructural y mortalidad proporcional. Se insinúa que la mortalidad por homicidio no permite que se exprese en el área de la salud los logros en el progreso social y los aportes de la salud pública en el período 1973 a 1996.